Arterial Stiffness Is Associated With Cytomegalovirus‐Specific Senescent CD8+ T Cells. Issue 9 (28th August 2017) - Yu, Hee Tae; Youn, Jong‐Chan; Kim, Jong Hoon; Seong, Yeon‐Jae; Park, Su‐Hyung; Kim, Hyeon Chang; Lee, Won‐Woo; Park, Sungha; Shin, Eui‐Cheol
Abstract : Background: Arterial stiffness is a well‐known predictor of future cardiovascular events. Search for the underlying mechanism of arterial stiffening is still under way. We investigated the relationship between arterial stiffness and cytomegalovirus infection in terms of T‐cell senescence. Methods and Results: Arterial stiffness was evaluated using pulse wave velocity measurements in 415 Koreans (age 59±12 years). We also investigated the frequency of CD57 + or CD28 null senescent T cells in peripheral blood lymphocytes and analyzed which immune parameters were correlated with pulse wave velocity. Furthermore, cytomegalovirus‐specific T cells were stimulated with overlapping peptides covering pp65 protein, and T‐cell function was evaluated by intracellular cytokine staining of interferon‐γ, tumor necrosis factor‐α, and CD107a. In a multivariate analysis, it was found that the frequency of CD57 + cells in the CD8 + T‐cell subset was independently correlated with pulse wave velocity after adjusting for traditional cardiovascular risk factors such as age, sex, diabetes mellitus history, smoking history, body mass index, blood pressure, serum creatinine, high‐density lipoprotein cholesterol, and high‐sensitivity C‐reactive protein. Cytomegalovirus pp65‐specific T cells were more frequently observed in the CD8 + CD57 + population than in the CD8 + CD57 − population, and multivariate analysis revealed that the frequency of cytomegalovirus pp65‐specific interferon‐γ +, tumor necrosis factor‐α +, or CD107a + cells in the CD8 + T‐cell subset was independently correlated with pulse wave velocity as well. Conclusions: We demonstrate that arterial stiffness is associated with senescent CD57 + T cells and CMV pp65‐specific T cells in the CD8 + T‐cell subset. The precise role of cytomegalovirus‐specific, senescent T cells in vascular aging needs to be further investigated.